A Giant on the Shoulders of Dwarfs: Archaeology and Recursion in Friedrich Kittler’s Works - Hron, Tania; Khaled, Sandrina (Journal of Contemporary Archaeology, 2015)
The essay explores the significance of archaeology and recursion in Kittler's works. The term recursion did not simply replace the term archaeology; it has become the paradigm for Kittler's history of being. Archaeology of knowledge can be described as following an iterative process, uncovering layers leading to the identification of recursive, self referential operations that shape technical innovation as well as concepts, thought and the conditions of reproduction: themes Kittler followed from Discourse Networks to Aphrodite and Eros. Recursion produces a better understanding based less in hermeneutical interpretation than in (data) processing.